Synthesis of Clay—Cerium Hydroxide Conjugates for the Adsorption of Arsenic - Yoshimi Seida; Yasuo Izumi (Adsorption Science & Technology)
Insoluble clay—cerium hydroxide conjugates exhibiting only limited swelling in water were synthesized for the removal of arsenic ions from aqueous solution. Thus, cerium hydroxide was immobilized electrostatically on the inner layer of highly dispersed Na-montmorillonite (clay). The clay + Ce(OH) n conjugate was prepared by intercalating colloidal cerium hydroxide in the clay inner layer. Similarly, the clay + Ce→OH conjugate was prepared by introducing cerium ions into the clay followed by their hydrolysis. The intercalation of cerium hydroxide and the chemical state of the cerium ion in the clay were evaluated via X-ray diffraction and X-ray absorption fine structure (XAFS) measurements. The conjugates exhibited a mesoporous structure with a high specific surface area of ca. 85–100 m 2 /g. These conjugates adsorbed As(III) and As(V) in a similar manner from aqueous solutions of As 2 O 3 and KH 2 AsO 4 , respectively, over the pH range 4–8. The adsorption isotherms for As(III) and As(V) onto the conjugates were Langmuirian in shape. They exhibited large values for the Langmuir constant, K, thereby indicating the effectiveness of the conjugates in the removal of arsenic ions from dilute aqueous solutions. The adsorption capacity of the clay + Ce→OH conjugate was superior to that of the clay + Ce(OH) n conjugate. Co-existing anions in the aqueous solutions such as chloride, carbonate, sulphate and phosphate had little effect on the removal of arsenic.